Performance Analysis of a Novel Nanofluid Assisted Thermoelectric Air Conditioner for Energy Efficient Building - Tan, Tai Keong (IRC, 2021)
The usage of thermoelectric air conditioning system in building application provides new alternative to conventional air conditioning system existed in the industry.